A More Nordic Norway? Examining Prisons in 21st Century Iceland. Issue 2 (19th January 2018) - PAKES, FRANCIS; GUNNLAUGSSON, HELGI
Abstract: This article seeks to examine the exact status of Iceland in light of the Nordic penal exceptionalism thesis. This thesis considers that punishment in the Nordic countries is fundamentally more benign than that in Anglophone countries (Pratt 2008a, 2008b). Yet from this perspective the remote Nordic country of Iceland remains overlooked. That is unfortunate as, at first sight, there is much to be intrigued about: Iceland's prison rate is very low; Iceland is small and homogeneous which may offer cultural or structural pre‐conditions for a positive penal system. Its penal estate is tiny with a small number of very small prisons. In addition, Iceland has a history of low crime rates and a tradition of lenient sentencing practices. All this makes it interesting to consider whether the penal exceptionalism thesis (Pratt and Eriksson 2011) actually extends to Iceland. To what extent does Iceland fit the Nordic mould of penal practice?